2022
DOI: 10.52728/ijjm.v3i1.392
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Business Performance on Credit Accessbility to Micro and Small Enterprises (MSEs)

Abstract: This study investigates the influence of performance of micro and small enterprises on accessing external finance from banks. This study used data from 30 respondents of MSEs by survey questionnaires in West Sumatera, Indonesia. The study used simple linear regression model with the access of credit as the dependent variable and performance of business as the independent variable. The results confirm that the performance of MSEs significantly affect accessibility to external finance from banks. The study recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This entails that there is a relationship between financial performance and access to finance by SMEs [79]. Existing studies submit that most lending institutions prefer firms that perform well over those that are not profitable [16,17]. Consistent with the Trade-off theory [80], being profitable means a business will have the ability to repay a loan without defaulting.…”
Section: Financial Performance and Access To Financementioning
confidence: 99%
See 3 more Smart Citations
“…This entails that there is a relationship between financial performance and access to finance by SMEs [79]. Existing studies submit that most lending institutions prefer firms that perform well over those that are not profitable [16,17]. Consistent with the Trade-off theory [80], being profitable means a business will have the ability to repay a loan without defaulting.…”
Section: Financial Performance and Access To Financementioning
confidence: 99%
“…In this case, banks usually prefer businesses with positive cashflows and traceable records of profitability [79]. Existing studies report that most profitable businesses do not usually experience barriers in accessing credit facilities [16,81]. There is evidence that financial performance positively predicts access to finance by SMEs [16,78,81].…”
Section: Financial Performance and Access To Financementioning
confidence: 99%
See 2 more Smart Citations
“…Business performance is a condition to be achieved as a result that all company components carried out. In this case, the business performance indicators are measured by the respondent's statement of changes in sales volume so that the company's existence is always carried out and constantly maintained so that it can find out consumer responses to the company's products (Chandrayanti, 2022). So it can be concluded that the performance of a business is everything that consumers want in a product or service by maximizing the quality of the results that consumers will receive.…”
Section: H1: Creative Intelligence Influences Competitive Advantage C...mentioning
confidence: 99%